Dinâmica de Carapa guianensis aubl. em Floresta Amazônica submetida a tratamentos silviculturais - Francez, Luciana Maria de Barros (2019)
This study aimed to evaluate the effect of silvicultural treatments on the structure, growth, and the dynamics of the community and population of Carapa guianensis Aubl., after 30 years of harvesting, in the Tapajós National Forest, Pará, in order to determine the most appropriate silvicultural treatment for the growth of the species. In 1981 and 1983, 60 plots of 50 x 50 m were randomly established, subdivided into 25 subplots of 10 x 10 m, where all trees with DBH ≥ 5 cm were measured. In each plot of 50 x 50 m, five subplots were sorted, and at the center of each one of those five, one plot of 5 x 5 m was allocated to measure the individuals of 2.5 cm ≤ DBH < 5 cm (sapling). Each plot of 5 x 5 m was divided into four triangles of 6.25 m², which one was sorted for the measurement of the seedlings (H ≥ 30 cm, DBH < 2.5 cm). Four treatments were established according to the different intensities of the silvicultural treatments, besides the control area (T0 – unlogged area; T1 – logged area; T2 – logged area + thinning up to 20%; T3 – logged area + thinning up to 40%; T4 – logged area + thinning up to 60%). The floristic diversity, phytosociology, diametric distribution, and natural regeneration rate of the forest and of C. guianensis were investigated. In addition, the probabilistic chain of transition to C. guianensis was done. The floristic revealed an area rich in terms of family, gender, and species. The species with the highest value of importance were Rinorea guianensis Aubl., Protium apiculatum Swart, and Rinorea Riana Kuntze. T1, T2, T3, T4 showed greater oscillation in density and species when compared with T0. The forest took on average 30 years to restore the initial basal area while C. guianensis did not resume the basal area before logging. Among the applied treatments, T2 presented the best increments of basal area, both for the community and for C. guianensis. In all treatments, mortality was higher than ingrowth, except for T4. Most trees, regardless of treatment, were more likely to remain in the same diametric class with a higher probability of mortality in small and medium diameter classes. The models generated through the Markov chain allow estimates with values close to those observed, although, it does not show efficiency regarding the disposition of the trees in the different diametric classes. The seedlings were more sensitive to the changes caused by the opening caused by the logging accompanied by the thinning; however, the sapling revealed a smaller number of individuals. Therefore, silvicultural interventions are necessary, through the enrichment and/or transplantation of young individuals as well as the amelioration of those already present in the area to ensure the resilience of C. guianensis and other species considered as commercial.